INCOME ELDERLY RELATIONSHIP WITH SOCIAL PERSONAL DEVELOPMENT OF 3-5 YEAR OLD IN THE TK LKMD VILLAGE OF RASNDUSARI TERAS BOYOLALI - Nur Kaisiyah Anisatul Khuluk; Sumantri .; Feri Catur Yuliani (STIKES DUTAGAMA KLATEN, 2014)
Background: The adequate family income will support grows child, because parents can provide all the needs of children both primary and secondary.Objectives: The purpose of this study to determine the relationship of income elderly with social personal development of 3-5 year old in the TK LKMD village of Randusari Teras Boyolali. Methods: This study was analical observational, with cross sectional design, time study conducted in November 2012 – August 2013. Population in this study is around the elderly and children in school in the TK LKMD Village Randusari Teras Boyolali, totaling 61 parents and children, sampling techniques by mean of purposive sampling with 54 correspondents in accordance with inclusion criteria. Results: There is a significant relationship between parental income with social personal development in children aged 3-5 years old kindergartens LKMD Randusari Village Terrace Boyolali, with p = 0.004 (ρ <0.05), so the hypothesis in this study received, but relationship is weak because the value of r = 0.388 approaching 0. The results of this study concluded that parents who have children aged 3-5 years income> 895,000 social development of their children tend to be normal personal. Conclusion: There is a significant relationship between parental income with social personal development in children aged 3-5 years old kindergartens LKMD Randusari Village Terrace Boyolali that hypothesis in this study received, but the relationship is weak because the value of r = 0.388 approaching 0.